Интеграция и регионализация в Европе: взгляд из Уэльса - Кононов, И. (Социология: теория, методы, маркетинг, 2001)
Рецензия: Wales Today / Ed. by D.Dunkerley, A.Thompson. — Cardiff: University of Wales Press, 1999. — 326 p. Dunkerley D., Hodgson L., Konopacki S., Spybey T., Thompson A. National and Ethnic Identity in the European Context. — Cardiff: Glamorgan University Press, 2000. — 233 p.